Declarative tactical knowledge from 12 to 22 years old in a professional football club: Real Sociedad - Sánchez-López, R.; Echeazarra, I.; Arrieta, J. M.; Castellano, J. (International Journal of Sports Science & Coaching, 2024)
This work aimed to measure and compare the declarative tactical knowledge (DTK) of the total number of academy players (n = 163; 16.75 ± 2.42 years) from the seven teams that make up the men's section of a Spanish professional football club. The `TESTACTICO for F7` tool was used to access the DTK of the participants in May 2022 (last part of the season), analysing the results obtained according to the age category (U14, U16, U19 and U23), and ensuring an adequate sample strength (f = 0.26) via G*Power. The analysis of variancewas used, through Tukey's HSD contrast test for post hoc multiple comparisons, evaluating the magnitude of the differences found by pairs of age categories through Cohen's d effect size. The macro-level comparisons between age categories evidenced differences (p = .017) with different effect sizes (2.17 < d > 0.55) in global, offensive and defensive scores, revealing two homogeneous groups: U14 + U16 and U19 + U23. In addition, the offensive score was higher than the defensive score in all age categories. At the meso-level, differences were found (p = .008) with different effect sizes (1.24 < d > 0.22) in 12 variables. At the micro-level, offensive behaviours outside of the game centre linked to depth, width and positioning, as well as defensive situations in which a tackle must be made are not declaratively dominated in any age category. It is concluded that, in a specific performance-oriented context, although the overall DTK scores are influenced by the age, different changes between age categories were verified.